Earnings, Productivity, and Performance‐Related Pay - Booth, Alison L.; Frank, Jeff (Journal of Labor Economics, 1999)
Jobs with performance-related pay (PRP) attract workers of higher ability and induce workers to provide greater effort. The authors construct an integrated model of effort and sorting that clarifies the distinction between observable and unobservable ability and the relationship between earnings and productivity. Predictions are tested against data from the British Household Panel Survey. The PRP raises wages by 9 percent for men and 6 percent for women. Theoretical calculations show that these estimated earnings differentials represent average productivity differentials net of monitoring costs at the marginal firm using PRP but not of the disutility of additional effort expended by workers. Copyright 1999 by University of Chicago Press.